Behavioral Predictors of Colonization with Lactobacillus crispatus or Lactobacillus jensenii after Treatment for Bacterial Vaginosis: A Cohort Study - Mitchell, Caroline (Hindawi Publishing Corporation, 2012)
Objective: Evaluate predictors of vaginal colonization with lactobacilli after treatment for bacterial vaginosis (BV). Methods. Vaginal fluid specimens from women with BV underwent qPCR for Lactobacillus crispatus, L. jensenii, and L. iners pre- and posttreatment. Results. Few women with BV were colonized with L. crispatus (4/44, 9%) or L. jensenii (1/44, 2%), though all had L. iners. One month posttreatment 12/44 (27%) had L. crispatus, 12/44 (27%) L. jensenii, and 43/44 (98%) L. iners. Presence of L. jensenii posttreatment was associated with cure (Risk Ratio (RR) 1.67; 95% CI 1.09–2.56); L. crispatus showed a similar trend (RR 1.41; 95% CI 0.89–2.24, P = 0.14). Receptive oral sex was associated with 2.2-log(10) lower concentration of L. crispatus (95% CI −4.38, −.02), and digital-vaginal sex with 2.6-log(10) lower concentration (95% CI −4.87, −.33). Conclusion. One month after BV treatment, few women established colonization with L. crispatus or L. jensenii. Few behaviors were associated with colonization.